Сorrosion and radiation resistance of potassium magnesium phosphate matrices - Sayenko, S.Y.; Shkuropatenko, V.A.; Zykova, A.V.; Surkov, O.Y.; Pylypenko, O.V.; Ulybkina, К.А.; Lobach, K.V. (Вопросы атомной науки и техники, 2018)
Corrosion and radiation resistances of potassium magnesium phosphate (PМP) matrices for hardening of liquid radioactive wastes of NPP were investigated. The high corrosion resistance of the PMP matrices to leaching of both basic components of matrix and cesium was shown. Results of performed work showed stability of physics and mechanical properties, as well as phase composition and microstructure of PMP after simulated γ-irradiation up to the absorbed dose 10⁸ rad. It was determined that irradiation by high-energy electrons to the absorbed dose 10¹⁰ rad results in partial dehydration and amorphization of PMP.